High intraspecific variability of Echinococcus granulosus sensu stricto in Chile. Issue 2 (April 2017) - Alvarez Rojas, Cristian A.; Ebi, Dennis; Paredes, Rodolfo; Acosta-Jamett, Gerardo; Urriola, Nicole; Roa, Juan Carlos; Manterola, Carlos; Cortes, Sandra; Romig, Thomas; Scheerlinck, Jean-Pierre; Lightowlers, Marshall W.
Abstract: Echinococcus granulosus sensu stricto is the major cause of cystic echinococcosis in most human and animal cases in the world and the most widespread species within the E . granulosus sensu lato complex. E . granulosus s . s . remains endemic in South America together with other species of the Echinococcus genus, especially in some areas in Argentina, Brazil, Chile and Peru. Except for a single human case caused by E . canadensis (G6) described in the literature, only E . granulosus s . s . has been found in the Chilean territory. In the current study 1609 bp of the cox 1 gene from 69 Chilean isolates of E . granulosus s . s . from humans and animals were analysed. In total, 26 cox 1 haplotypes were found, including the widespread haplotype EG01 (22 isolates) and also EGp1 (5), EgRUS7 (1), EgAus02 (1) and EgAus03 (2). Twenty-one different haplotype not previously described were identified from 38 Chilean isolates designated EgCL1–EgCL21. Previous work had described low variability of E . granulosus s . s . in South America, based on isolates from Peru. Results obtained in this work challenge the previously described idea of the low diversity of the parasite in South America, and warrant future investigation on the origin and spread of the parasite in the continent after the Spanish arrival.